Paravertebral Block versus Thoracic Epidural Analgesia for Postthoracotomy Pain Relief: A Meta-Analysis of Randomized Trials - Xu, Mu; Hu, Jiajia; Yan, Jianqin; Yan, Hong; Zhang, Chengliang (The Thoracic and Cardiovascular Surgeon, 2021)
Objective Paravertebral block (PVB) and thoracic epidural analgesia (TEA) are commonly used for postthoracotomy pain management. The purpose of this research is to evaluate the effects of TEA versus PVB for postthoracotomy pain relief.Methods A systematic literature search was conducted in PubMed, EMBASE, Web of Science, and the Cochrane Library (last performed on August 2020) to identify randomized controlled trials comparing PVB and TEA for thoracotomy. The rest and dynamic visual analog scale (VAS) scores, rescue analgesic consumption, the incidences of side effects were pooled.Results Sixteen trials involving 1,000 patients were included in this meta-analysis. The pooled results showed that the rest and dynamic VAS at 12, 24, and rest VAS at 48 hours were similar between PVB and TEA groups. The rescue analgesic consumption (weighted mean differences: 3.81; 95% confidence interval [CI]: 0.982–6.638, p < 0.01) and the incidence of rescue analgesia (relative risk [RR]: 1.963; 95% CI: 1.336–2.884, p < 0.01) were less in TEA group. However, the incidence of hypotension (RR: 0.228; 95% CI: 0.137–0.380, p < 0.001), urinary retention (RR: 0.392; 95% CI: 0.198–0.776, p < 0.01), and vomiting (RR: 0.665; 95% CI: 0.451–0.981, p < 0.05) was less in PVB group.Conclusion For thoracotomy, PVB may provide no superior analgesia compared with TEA but PVB can reduce side effects. Thus, individualized treatment is recommended. Further study is still necessary to determine which concentration of local anesthetics can be used for PVB and can provide equal analgesic efficiency to TEA.
Keywords: paravertebral block; epidural analgesia; thoracotomy; pain relief; meta-analysis